1024. Transitions of Care Quality Metrics in Patients Discharged on Parenteral Antimicrobial Therapy in a Large Urban Hospital that Lacks a Formal Outpatient Parenteral Antimicrobial Therapy Program. (15th December 2022) - Schultz, Sara K; Minuk, Jeffrey; Rodriguez, Leah
Abstract: Background: With the evidence demonstrating the need for antimicrobial stewardship in the transition from inpatient to outpatient intravenous (IV) antibiotic therapy, it is imperative to have effective communication and coordination in a multidisciplinary team. Studies have demonstrated the utility of initiating a formal Outpatient Parenteral Antimicrobial Therapy (OPAT) program. The goal of this study is to assess quality metrics in a sample of patients discharged on IV antibiotics prior to initiation of a pilot OPAT program. Methods: This is a retrospective, multicenter chart review of patients admitted to Temple University Health System from 10/1/2020 - 10/31/2021 who were discharged on IV antibiotics. There were no exclusion criteria. Patients with multiple admissions were documented as separate occurrences. Qualitative data were collected on the appropriateness of OPAT indication, pathogens targeted, antibiotics used, performance of infectious diseases (ID) consult, line selected, outcomes, and demographics. The primary endpoint is the percentage of global IV antibiotic prescribing errors (antibiotic, dose, route, frequency, duration, parenteral access device). Results: There were 748 total discharges on IV antimicrobials in 705 unique patients. We chose a random sample of 109 discharges. Twenty (18%) had an oral antimicrobial available as an option. Antibiotic selection, dosing, duration, and access were correct 92%, 82%, 64% and 65% respectively (Table 2). ID recommended laboratory monitoring for 44 (40%) patients, of which 8 (18%) were sent to ID clinic; all had abnormal findings. Of the 25 patients who required ID follow-up, 11 had a scheduled ID appointment of which 8 attended. There was no mortality within 30 days from the 8 patients, but 2 were readmitted within 30 days. Overall, 39% patients readmitted within 30 days, 6% had mortality within 30 days and 50% were known to have completed therapy. Conclusion: Our study captured a 65% rate of prescribing errors in a sample of 109 patients receiving IV antibiotics at discharge. The findings demonstrate an urgent need for an OPAT program to help with antimicrobial, parenteral access selection, monitoring, and follow-up with ID. By implementing this program, we hope to improve our ID follow-up, lab monitoring, and readmission metrics. Disclosures: All Authors : No reported disclosures.